The effects of long term physsical exercise on haemotological and some biochemical parameters in horses - Hasan Güzelbekteş; Mahmut Ok; İsmail Şen; Alparslan Coşkun (Eurasian Journal of Veterinary Sciences)
In this study, the effects of intensive physical exercise on haematological {RBC, WBC, Hgb, Ht) and some biochemical (T.P, albumin, glikoz, BUN, ALT, ALP, AST, LDH, GGT, CK, Creatinin, Na^ ve TCa"-) parameters in marriageable horses were investigated. 34 female crossbred England Horses (7-10 years old) were used in this study. Horses were exercised four hours daily for 10 days on dry sand and closed manage. In compared all parameters before and after exercise, WBC (p<0.05), Ht (p<0.05), TP (p<0.05), Albumin (p<0.05), Glikoz (p<0.05), BUN (fx0.05), AST (p<0.05), LDH (p<0.05), CK (p<0.005) and Na++(p<0.05) were increased statistically after exercise compared with before exercise. In conclusion, the results of this study indicated that long tenm trained in horse would be cause to changed serious on some haemotological and biochemical parameters.